Acetylcholine and ethylene: do they share similar receptors and biological action? - Kurchii, B.A. (Інститут молекулярної біології і генетики НАН України, 2009)
From chemical point of view acetylcholine (ACh) is a quaternary ammonium salt whose biological importance is connected with its role as a neurotransmitter between neurones and other neurocellular junctions. Earlier we have postulated (Kurchii, 1998) and then confirmed (Kurchii, Kurchii, 2000) that ACh under influence of physiological solution and alkaline mixture was decomposed with releasing of ethylene. Unfortunately using gas chromatograph we could not detected another two peaks on the chromatogram (Kurchii, Kurchii, 2000). Here we identified one of two unknown peaks: it is ethylene oxide. We have revealed that ethylene oxide was released in the quantity much more than ethylene during 10-20 min of decomposition in air or in drop of physiological solution. We have concluded that biological effects of ACh can be caused by action of ethylene oxide that is a very reactive agent and this is a prompt effect for short distance. Ethylene can migrate on the long distance and cause slow effects, but it should be preliminary activated because under normal conditions (temperature and pressure) it is a very inert chemical and cannot react with any substance. Nevertheless, it can be in vivo activated in the free radical addition reactions. Also as follows from our results the question about specific receptors for ACh is questionable.